Benchmarking glycoform-resolved affinity separation – mass spectrometry assays for studying FcγRIIIa binding - Gstöttner, Christoph; Lippold, Steffen; Hook, Michaela; Yang, Feng; Haberger, Markus; Wuhrer, Manfred; Falck, David; Schlothauer, Tilman; Domínguez-Vega, Elena (Frontiers in Immunology, 2024)
The antibody- FcγRIIIa interaction triggers key immunological responses such as antibody dependent cellular cytotoxicity (ADCC), making it highly important for therapeutic mAbs. Due to the direct glycan-glycan interaction with FcγRIIIa receptor, differences in antibody glycosylation can drastically influence the binding affinity. Understanding the differential binding of mAb glycoforms is a very important, yet challenging task due to the co-existence of multiple glycoforms in a sample. Affinity liquid chromatography (AC) and affinity capillary electrophoresis (ACE) hyphenated with mass spectrometry (MS) can provide glycoform-resolved affinity profiles of proteins based on their differences in either dissociation (AC) or equilibrium (ACE) constants. To cross-validate the affinity ranking provided by these complementary novel approaches, both techniques were benchmarked using the same FcγRIIIa constructs. Both approaches were able to assess the mAb – FcγRIIIa interaction in a glycoform selective manner and showed a clear increase in binding for fully versus hemi-fucosylated mAbs. Also, other features, such as increasing affinity with elevated galactosylation or the binding affinity for high mannose glycoforms were consistent. We further applied these approaches to assess the binding towards the F158 allotype of FcγRIIIa, which was not reported before. The FcγRIIIa F158 allotype showed a very similar profile compared to the V158 receptor with the strongest increase in binding due to afucosylation and only a slight increase in binding with additional galactosylation. Both techniques showed a decrease of the binding affinity for high mannose glycoforms for FcγRIIIa F158 compared to the V158 variant. Overall, both approaches provided very comparable results in line with orthogonal methods proving the capabilities of separation-based affinity approaches to study FcγR binding of antibody glycoforms.